Reforma educacional e prática docente: o discurso sobre a apropriação dos seus fundamentos na escola - Valéria Andrade Silva; Miguel Henrique Russo (EccoS – Revista Científica)
In this text we summarize the data and discussions of an investigation made at a São Paulo public state school which aimed to verify how teachers have appropriated the foundations and central ideas of the educational reform promoted during Serra's government through an Action Plan followed by the program "São Paulo faz escola" which refers to the curricular dimension of the reform. The data were collected from interviews, observations and documental analysis of teaching plans. The results revealed that teachers made quite a partial appropriation of the conceptual basis of the curricular proposal and that their practice confirms the tenet of curriculum being the action developed in the school practice mediated by the teachers' appropriation of the reformers ideas.